Abrocitinib: A Comprehensive Review of its Efficacy and Safety in Dermatology - Sunil Dogra; Shikha Shah; Manavi Gupta; Ayush Sharma; Seema Chhabra (Wolters Kluwer Medknow Publications, 2024)
Abrocitinib is a novel oral small molecule which acts as a selective JAK-1 inhibitor. Currently approved for use in moderate-to-severe cases of atopic dermatitis, this drug is gaining a rapid impetus for its use across various inflammatory dermatoses for its selective downstream action on cytokines of the JAK-1 pathway. Its efficacy and safety in atopic dermatitis has been established in phase 3 clinical trials. The future implication of this drug will depend largely on feasibility and practical use in Indian scenario.